Macrophage inhibitory cytokine‐1 is associated with cognitive impairment and predicts cognitive decline – the Sydney Memory and Aging Study. Issue 5 (19th July 2013) - Fuchs, Talia; Trollor, Julian N.; Crawford, John; Brown, David A.; Baune, Bernhard T.; Samaras, Katherine; Campbell, Lesley; Breit, Samuel N.; Brodaty, Henry; Sachdev, Perminder; Smith, Evelyn
Summary: Higher levels of macrophage inhibitory cytokine‐1, also known as growth differentiation factor 15 (MIC‐1/GDF15), are associated with adverse health outcomes and all‐cause mortality. The aim of this study was to examine the relationships between MIC‐1/GDF15 serum levels and global cognition, five cognitive domains, and mild cognitive impairment (MCI), at baseline (Wave 1) and prospectively at 2 years (Wave 2), in nondemented participants aged 70–90 years. Analyses were controlled for age, sex, education, Framingham risk score, history of cerebrovascular accident, acute myocardial infarction, angina, cancer, depression, C‐reactive protein, tumor necrosis factor‐α, interleukins 6 and 12, and apolipoprotein ε4 genotype. Higher MIC‐1/GDF15 levels were significantly associated with lower global cognition at both waves. Cross‐sectional associations were found between MIC‐1/GDF15 and all cognitive domains in Wave 1 (all P < 0.001) and between processing speed, memory, and executive function in Wave 2 (all P < 0.001). Only a trend was found for the prospective analyses, individuals with high MIC‐1/GDF15 at baseline declined in global cognition, executive function, memory, and processing speed. However, when categorizing MIC‐1/GDF15 by tertiles, prospective analyses revealed statistically significant lower memory and executive function in Wave 2 in those in the upper tertile compared with the lower tertile. Receiver operating characteristics (ROC) analysis was used to determine MIC‐1/GDF15 cutoff values associated with cognitive decline and showed that a MIC‐1/GDF15 level exceeding 2764 pg/ml was associated with a 20% chance of decline from normal to MCI or dementia. In summary, MIC‐1/GDF15 levels are associated with cognitive performance and cognitive decline. Further research is required to determine the pathophysiology of this relationship.